text Rekonstruksi Makna Remaja yang Mampu Sebagai Batas Kedewasaan dalam Mencegah Perkawinan Dini di Kabupaten Polewali mandar (Perspektif Hukum Islam): articel text - Ramlan, Amalia; Syam, Hikmatul Adhiyah; Syam, Nur Fakhirah; Haq, Ahmad Ya'rif (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Early marriage remains an urgent socio-legal issue with multidimensional impacts on health, education, and family resilience, particularly in Polewali Mandar Regency, which has the highest rate of teenage marriage in Indonesia. One of the main factors behind this phenomenon is the ambiguous interpretation of the concept of “capable adolescents” as a threshold of maturity, which is often narrowly understood only through biological indicators without considering psychological, social, and economic readiness. This study aims to reinterpret the meaning of “capable adolescents” within the framework of Islamic law and assess its relevance to contemporary social realities in efforts to prevent early marriage. The research method used is a normative juridical approach supported by a sociological approach, through a study of classical and contemporary Islamic legal sources, analysis of legislation, and interviews with adolescents who married at an early age, the community, and religious leaders. The results of the study show that although Islamic law traditionally determines maturity based on signs of puberty and interprets the term syabab (adolescent/youth) as the ability to bear the responsibilities of marriage physically, financially, and socially, these criteria have proven to be insufficient in the current social context. This study emphasizes that maturity must also include mental readiness, intellectual and emotional maturity (rushd), as well as spiritual and social competence. This comprehensive approach is in line with the provisions of Marriage Law No. 16 of 2019, which sets a minimum age for marriage, thereby strengthening the preventive framework in curbing the practice of early marriage. A more holistic reinterpretation of the concept of “capable adolescents” is an important basis for strategies to prevent early marriage through the synergy of Islamic law, positive law, the role of the family, and educational institutions in building public awareness of the importance of age readiness and maturity before marriage.